Association Between First-Trimester Maternal Cytomegalovirus Infection and Stillbirth: A Prospective Cohort Study - Song, Xinli; Li, Qiongxuan; Diao, Jingyi; Li, Jinqi; Li, Yihuan; Zhang, Senmao; Chen, Letao; Wei, Jianhui; Shu, Jing; Liu, Yiping; Sun, Mengting; Sheng, Xiaoqi; et al. (Frontiers in Pediatrics, 2022)
Background: Cytomegalovirus (CMV) infection during pregnancy as a cause of stillbirth was overlooked to some extent. This was the first prospective cohort study to assess the effect of maternal CMV infection during pregnancy on stillbirth. Methods: This study recruited 44048 eligible pregnant women from March 13, 2013 to December 31, 2019. CMV-specific IgM and IgG, and IgG avidity index were measured with automated chemiluminescence immunoassay. The association was assessed using the inverse probability of group-weighted multivariate-adjusted log-binomial models. Results: 540 infants ended with a stillbirth (12.3 per 1000 pregnancies), and 2472 pregnancies with maternal CMV infection were screened out (56.1 per 1000 pregnancies) among all eligible pregnancies. In the comparison analysis, 326 infants ended with a stillbirth (86.6 per 1000 pregnancies) in the maternal CMV infection group compared with 214 infants (7.8 per 1000 pregnancies) in the group where mothers were not infected with CMV (RR 12.17; 95% CI 9.43-15.71). After excluding the pregnancies of stillbirth with birth defects, a strong association between the two groups was still observed (RR 9.38; 95% CI 6.92-12.70). Conclusions: Our findings suggested maternal CMV infection could significantly increase the risk of stillbirth in offspring, which had important directive significance in the actual hygiene consultation.